EFEK MODERASI UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA DITINJAU DARI ARUS KAS BEBAS, LEVERAGE DAN KUALITAS AUDIT - Amilah, Siti; Mutmainah, Ina (UNPERBA, 2025)
Earnings management is an action carried out by a manager by manipulating financial reports with the aim of benefiting himself (the manager) and the company's profits. This research aims to determine the effect of free cash flow, leverage and audit quality on earnings management, moderated by company size. The population in this research is 55 companies in the consumer goods industry sector listed on the IDX in 2019-2023. The sampling technique in this research was purposive sampling. The sample in this research was 15 companies. This research uses a multiple linear regression test data analysis method with the IBM SPSS Statistics 26 program. The results of this research indicate that leverage and audit quality have a positive and significant effect on earnings management. Meanwhile, free cash flow has no negative and significant effect on earnings management. Company size is able to strengthen free cash flow, leverage, and audit quality on earnings management.